Women, social justice, and human rights - Devasia, V. V.; Devasia, Leelamma (New Delhi : APH Pub. Corpn., 1998)
With reference to India.
Includes bibliographical references and index.
Keywords: Women -- India -- Social conditions; Human rights -- India; Women's rights -- India